(x-9)(x-3), because -9 and -3 make a sum of -12 and a product of +27
Answer:
It's 14.
Step-by-step explanation:
Google. ;)
Answer: 91/167
Explanation:
Answer:
x=-2/5
Step-by-step explanation:
4(-3x-1)=13x+6 ~ Distribute the 4 into the parenthesis
-12x-4 = 13x+6 ~ add 12x to both sides
-4= 25x + 6 ~ subtract 6 from both sides
-10 =25x ~ divide by 25
-10/25 = x ~ simplify the fraction by dividing the num. and den by 5
-2/5 =x
Answer:
<u>Hi there your correct answer to this is D. a high interest rate.</u>
Hope it helps! ;>